A content analysis of South African media coverage of China during the FOCAC 2015 Johannesburg summit - Yu, Meng (My University, 2018)
Previous studies on South African media responses to the developing China-South Africa relationship show there is a disparity between the media representation of China versus the official tone set by the two governments for their bilateral relationship. This paper compares how two SouthAfrican newspapers,The NewAge andThe Citizen, located at the opposite ends of political spectrum, reported on China during a six month period which approximates the duration of the Forum of China Africa Cooperation Sixth Ministerial Conference also known as The Johannesburg Summit. The aim of this comparison is to map the media factors leading to these differences. Before delving into the content analysis, the study first reviewed the media frames of China in Africa using the political economy of media theory. The triangulation of these theories linked the frames to the political economic orientation of the chosen newspapers. A quantitative content analysis of The New Age and The Citizen was conducted focusing on topics, tones, sources and theframeswhichweresummarisedfromChinaAfricaacademicliterature. Results disclosed both The New Age and The Citizen had business and commerce topics as the main point of interest. Other aspects of the bilateral relationship were not receiving much media attention despite government efforts. The Citizen had more coverage, although negative, of the JohannesburgSummit with diverse topics, different tones and sources thanThe NewAge. Judging by application of the frames, The Citizen showed an editorial leaning towards the opposition of the ruling party, and economic orientation towards its elite readers. Content analysis also confirmed the government-control nature of The New Age. China was more positively portrayed in The New Age. The research proves that ownership and funding had shaped South African mediarepresentationofChina
A research report submitted in impartial fulfillment of the requirements for a Master of Arts degree in Journalism and Media Studies by course work and research at University of the Witwatersrand , March 2018
Keywords: South African Broadcasting Corporation; Mass media--South Africa